8th Workshop on Cloud Technologies in Education: Report - Serhiy O. Semerikov; Mariya P. Shyshkina; Andrii M. Striuk; Mykola I. Striuk; Iryna S. Mintii; Olga O. Kalinichenko; Larisa S. Kolgatina; Maryna Ye. Karpova (Academy of Cognitive and Natural Sciences, 2021)
This is an introductory text to a collection of selected papers from the 8th Workshop on Cloud  Technologies in Education (CTE 2020) which was held in Kryvyi Rih, Ukraine, on the December 18, 2020.  It consists of short introduction, papers' review and some observations about the event and its future.